Arc of Interference : Medical Anthropology for Worlds on Edge - Adams, Vincanne, 1959-; Biehl, João Guilherme (Book collections on Project MUSE., 2023)
"The radically humanistic essays of Arc of Interference refigure our sense of the real, the ethical, and the political in the face of mounting social and planetary upheavals. Creatively assembled around Arthur Kleinman's medical anthropological arc and eschewing hegemonic modes of intervention, they advance the notion of a care-ful ethnographic praxis of interference. To interfere is to dislodge ideals of naturalness, blast enduring binaries (human-nonhuman, self-other, us-them), and redirect technocratic agendas while summoning relational knowledge and the will to create community. The book's multiple ethnographic arcs of interference provide a vital conceptual toolkit for today's world and a badly needed moral perch to peer toward just horizons. Contributors. Vincanne Adams, João Biehl, Davíd Carrasco, Lawrence Cohen, Jean Comaroff, Robert Desjarlais, Paul Farmer, Marcia Inhorn, Janis H. Jenkins, David S. Jones, Salmaan Keshavjee, Arthur Kleinman, Margaret Lock, Adriana Petryna"--